Long-Term Oxygen Therapy in Chronic Obstructive Pulmonary Disease - Yuni Ekowati (Indonesian Journal of Physical Medicine & Rehabilitation, 2015)
Chronic Obstructive Pulmonary Disease (COPD) affects 210 million people worldwide and is predicted to increase more than 30% in the ten following years. Long-term oxygen therapy (LTOT) is the treatment of choice nowadays and widely used to reduce mortality in COPD. LTOT in COPD can improve hemodynamic status, exercise tolerance, dyspnoea, life expectancy, quality of life, cognitive function and frequency of hospitalization.The success of LTOT depends on patient compliance, duration of therapy and the accuracy of hypoxemia correction. Although LTOT provides many benefits in COPD patients, but it also has many disadvantages. Subjective factor is the determinant factor in the success of therapy. Follow-up session is required to evaluate the therapeutic efficacy, prevent side effects and detect any clinical deterioration or hypercapnia as early as possible for an immediate referral to the hospital.Keywords: Long-term Oxygen Therapy (LTOT), COPD, hypoxemia,quality of life.